LAWYERS, LAW REPORTING AND THE SHARIA COURTS OF APPEAL IN NIGERIA - Oba, Abdulmumini Adebayo (Jurnal Syariah, 2023)
The Sharia Court of Appeal (first created in 1960) is a superior court of record that hears appeals from the area courts and Sharia courts in Islamic personal law cases only. Appeals from the Sharia Courts of Appeal go to the Court of Appeal and finally, to the Supreme Court. Lawyers gained the right of audience in the Sharia Courts of Appeal and qualified for appointment as Kadis of the court in 1985 and 1999 respectively. Reports of the Sharia Courts of Appeal judgments are hard to come by. An exception is the Kwara State Sharia Court of Appeal that has published its Annual Reports for the years 1993 to 2015. The Annual Report was renamed Law Reports and the Law Reports for 2016 and 2020 have been published. This paper gives a conceptual and historical background to Islamic law reporting, analyses the 2000 Annual Report and 2020 Law Report (the maiden editions respectively) and examines the prospects of reporting cases of the court. The study finds some differences in the formats of the annual reports and the law reports; inconsistencies in the court’s referencing style and the transliteration schemes, and that the reports are useful to lawyers and academics alike. The paper recommends that the judgments in the court should not be unduly long; that the referencing style and transliteration scheme for Arabic sources should be standardized; and that while the reports be encouraged and sustained, the concept of stare decisis should not become entrenched in Islamic courts.